Критеріальне моделювання якості фунціонування автоматичних систем керування - Комар, В. О.; Лесько, В. О. (Видавництво Національного університету «Львівська політехніка», 2007)
The method of getting criteria quality functioning of automatically control systems based at association of the theory of Markov processes and criterion modeling is considered in given article.